Cross-Platform Short-Video Diplomacy: Topic and Sentiment Analysis of China–US Relations on Douyin and TikTok - Wei, Zheng; Li, Mingchen; Liao, Junxiang; Yang, Zeyu; Yang, Xiaoyu; Xie, Yixuan; Hui, Pan; Qu, Huamin (Proceedings of the International AAAI Conference on Web and Social Media, 2026)
We examine discussions surrounding China-U.S. relations on the Chinese and American social media platforms Douyin and TikTok. Both platforms, owned by ByteDance, operate under different regulatory and cultural environments, providing a unique perspective for analyzing China-U.S. public discourse. This study analyzed 4,040 videos and 338,209 user comments to assess the public discussions and sentiments on social media regarding China-U.S. relations. Through topic clustering and sentiment analysis, we identified key themes, including economic strength, technological and industrial interdependence, cultural cognition and value pursuits, and responses to global challenges. There are significant emotional differences between China and the US on various themes. Since April 2022, the Chinese government has implemented a new regulation requiring all social media accounts to disclose their provincial-level geolocation information. Utilizing this publicly available data, along with factors such as GDP per capita, minority index, and internet penetration rate, we investigate the changes in sentiment towards the U.S. in mainland China. This study links socioeconomic indicators with online discussions, deeply analyzing how regional and economic factors influence Chinese comments on their views of the US, providing important insights for China-U.S. relationship research and policy making.